Floral reward, advertisement and attractiveness to honey bees in dioecious Salix caprea. - Stefan Dötterl; Ulrike Glück; Andreas Jürgens; Joseph Woodring; Gregor Aas (PLoS ONE)
In dioecious, zoophilous plants potential pollinators have to be attracted to both sexes and switch between individuals of both sexes for pollination to occur. It often has been suggested that males and females require different numbers of visits for maximum reproductive success because male fertility is more likely limited by access to mates, whereas female fertility is rather limited by resource availability. According to sexual selection theory, males therefore should invest more in pollinator attraction (advertisement, reward) than females. However, our knowledge on the sex specific investment in floral rewards and advertisement, and its effects on pollinator behaviour is limited. Here, we use an approach that includes chemical, spectrophotometric, and behavioural studies i) to elucidate differences in floral nectar reward and advertisement (visual, olfactory cues) in dioecious sallow, Salix caprea, ii) to determine the relative importance of visual and olfactory floral cues in attracting honey bee pollinators, and iii) to test for differential attractiveness of female and male inflorescence cues to honey bees. Nectar amount and sugar concentration are comparable, but sugar composition varies between the sexes. Olfactory sallow cues are more attractive to honey bees than visual cues; however, a combination of both cues elicits the strongest behavioural responses in bees. Male flowers are due to the yellow pollen more colourful and emit a higher amount of scent than females. Honey bees prefer the visual but not the olfactory display of males over those of females. In all, the data of our multifaceted study are consistent with the sexual selection theory and provide novel insights on how the model organism honey bee uses visual and olfactory floral cues for locating host plants.